Improved characterization and translation of NK cells for canine immunotherapy - Razmara, Aryana M.; Gingrich, Alicia A.; Toedebusch, Christine M.; Rebhun, Robert B.; Murphy, William J.; Kent, Michael S.; Canter, Robert J. (Frontiers in Veterinary Science, 2024)
The field of cancer immunology has seen a meteoric rise in interest and application due to the discovery of immunotherapies that target immune cells, often leading to dramatic anti-tumor effects. However, successful cellular immunotherapy for solid tumors remains a challenge, and the application of immunotherapy to dogs with naturally occurring cancers has emerged as a high yield large animal model to bridge the bench-to-bedside challenges of immunotherapies, including those based on natural killer (NK) cells. Here, we review recent developments in the characterization and understanding of canine NK cells, a critical springboard for future translational NK immunotherapy research. The characterization of canine NK cells is exceptionally pertinent given the ongoing challenges in defining them and contextualizing their similarities and differences compared to human and murine NK cells compounded by the limited availability of validated canine specific reagents. Additionally, we summarize the current landscape of the clinical and translational literature employing strategies to capitalize on endogenous and exogenous NK cell immunotherapy in canine cancer patients. The insights regarding efficacy and immune correlates from these trials provide a solid foundation to design and test novel combinational therapies to enhance NK cell activity with the added benefit of motivating comparative work to translate these findings to human cancers with extensive similarities to their canine counterparts. The compilation of knowledge from basic canine NK phenotype and function to applications in first-in-dog clinical trials will support the canine cancer model and enhance translational work to improve cancer outcomes for both dogs and humans.